2016
DOI: 10.1590/1678-4324-2016150666
|View full text |Cite
|
Sign up to set email alerts
|

40K, 226Ra AND 228Ra SERIES IN BOVINE AND POULTRY FEED AND IN DICALCIUM PHOSPHATE (DCP) SAMPLES BY GAMMA-RAY SPECTROMETRY

Abstract: K activity has reached hundreds of Becquerel in feed samples, it should not represent a risk to human health, not even to animals, since potassium is an essential mineral to living organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(23 reference statements)
1
2
0
1
Order By: Relevance
“…The 40 K concentration obtained is similar to what was obtained in Egypt (Harb et al, 2010) but higher for 226 Ra and 232 Th. In Brazil, a higher concentration of 40 K was reported in poultry feeds (Filho et al, 2016). Similarly, a higher concentration of 40 K than the present study was reported in Benue and Kaduna states, Nigeria (Ageda et al, 2017).…”
Section: Internal Risk Indexsupporting
confidence: 65%
See 2 more Smart Citations
“…The 40 K concentration obtained is similar to what was obtained in Egypt (Harb et al, 2010) but higher for 226 Ra and 232 Th. In Brazil, a higher concentration of 40 K was reported in poultry feeds (Filho et al, 2016). Similarly, a higher concentration of 40 K than the present study was reported in Benue and Kaduna states, Nigeria (Ageda et al, 2017).…”
Section: Internal Risk Indexsupporting
confidence: 65%
“…To this end, supplementary minerals were added to stimulate growth (Scheibel et al, 2006). Also, some feed produced from plants and animal sources (organic base) to give complete nutrition for the birds contains organic matter (Filho et al, 2016). These feeds may also contain natural radionuclides that may contaminate the poultry feeds (Ageda et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porém este processo não garante a retirada dos radionuclídeos naturais, como pode ser observado na Tabela 2, onde as concentrações de 228 Ra e 226 Ra variaram significativamente. A concentração média de 228 Ra e 226 Ra em amostras de fosfato bicalcico produzido no Brasil variou de 4.200 a 8.300 mBq.kg -1 na matéria seca, respectivamente [22]. Esses valores estão na mesma faixa de variação daqueles apresentados na Tabela 2.…”
Section: Resultsunclassified